Role of nanotechnology in climate change mitigation: Opportunities, challenges, and future directions - Musa , Abubakar H.; Musa, Shuaibu S.; Alhassan, Muhammad Y.; Okesanya, Olalekan J.; Ishak, Abubakar S.; Auwal, Auwal R.; Alaka, Hassan O.; Othman, Zhinya K.; Ibrahim, Adamu M.; Sy, Francis AR.; Ahmed, Mohamed M.; Kouwenhoven, MBN.; Lucero-Prisno III, Don E. (Narra Sains Indonesia, 2025)
Climate change, recognized as one of the most critical global public health emergencies, has led to extreme weather events and caused thousands of deaths annually, particularly in underserved areas due to limited financial resources. Nanotechnology, with its unique quantum properties, enhanced surface area, and heightened reactivity, has emerged as a promising tool for climate crisis management. The aim of this study was to explore the role of nanotechnology in mitigating climate change, offering insights into the opportunities and challenges associated with its deployment. Nanotechnology has transformed the renewable energy field by advancing sustainability, improving efficiency, and reducing costs. Nanomaterial also enhances the effectiveness of carbon capture and conversion processes, providing a viable path in the fight against climate change. Additional opportunities include lowering greenhouse gas emissions, improving energy conservation, and enabling cleaner technologies. Furthermore, nanotechnology holds the potential to revolutionize the mitigation of air, water, and land pollution, contributing to a more climate-resilient environment and supporting global climate goals. Despite these opportunities, its integration into climate change mitigation poses significant obstacles. Concerns include the generation of reactive oxygen species that may induce cellular dysfunction and carcinogenesis, as well as challenges related to sophisticated manufacturing processes, high material costs, and inadequate policy frameworks. While nanotechnology demonstrates significant potential in mitigating the effects of climate change, future studies should focus on comprehensive safety evaluations, cost-effective production methods, and strategies to minimize long-term environmental and health effects to ensure its sustainable and responsible application.